Beyond the wired backhaul: a system-level perspective of heterogeneous networks with wireless backhaul for 5G and beyond - Silva, Gabriel Carlini Monte da (2024)
The fifth generation (5G) of cellular wireless networks incorporated the millimeter waves. One of the drawbacks of these higher frequencies is the severe propagation losses compared to sub-6 GHz spectrum. One possible solution to mitigate that is the network densification, which is the deployment of more nodes in the environment. For this, heterogeneous networks (HetNets) have been deployed. HetNets are different types of nodes beyond traditional next generation node B (gNB). Three examples of new nodes that have been considered are integrated access and backhaul (IAB) nodes, network-controlled repeaters (NCRs) and reconfigurable intelligent surfaces (RISs). IAB is a decode and forward node, while NCR is an amplify and forward node. RIS is a device that manipulates impinging electromagnetic waves using a metamaterial layer. This master thesis presents an overview regarding these nodes. They have been deployed with different levels of mobility, e.g, fixed, nomadic and mobile. Thus, this work also presents an overview regarding unmanned aerial vehicles (UAVs) that can be deployed together with these nodes to give them aerial mobility. Furthermore, a system level model is defined allowing a performance evaluation of these nodes. Moreover, it is evaluated the impact of deploying these nodes aiming at enhancing the performance of a network used to cover an outdoor sport event. It is also evaluated the impact on fixed IAB and NCR of the change on the backhaul link from line of sight (LOS) to non-line of sight (NLOS). This work also analyzes the performance improvement due to deployment of NCR on a given cell and its interference impact on neighbor cells. Simulation results show the improvement in user equipments (UEs)’ signal to interference-plus-noise ratio and throughput due to the deployment of these nodes. In the considered scenario, in general, IAB presented the best performance followed by NCR and RIS. However, there were situations where NCR outperformed IAB due to higher level of interference caused by the latter. Moreover, the deployment of these nodes in UAVs also achieved performance gains, however their energy limitations prevented them from reaching results as good as the ones achieved by their fixed deployment. The change in backhaul condition from LOS to NLOS affected the performance of fixed IAB and NCR. NCR was the one which suffered the most. It highlights the importance of a good network planning. If fixed nodes present challenging backhaul conditions, it should be considered the deployment of UAV nodes. Finally, the results also showed that the negative impact on neighbor UEs of receiving interference from NCR signals of other cells was not enough to put them on outage. Besides, this interference can be mitigated by proper NCR beam management.